Ionospheric electron density over Resolute Bay according to E-CHAIM model and RISR radar measurements. Issue 6 (15th March 2023) - Larson, B.; Koustov, A.V.; Themens, D.R.; Gillies, R.G.
Highlights: Ratios of E-CHAIM model-to-RISR radar measured electron density are close to one at heights near F2 peak. On average, E-CHAIM underestimates electron density at ionospheric topside and bottomside by ∼ 20 % E-CHAIM underestimations are strongest in summer and equinoctial nighttime at bottomside and in autumn nighttime at topside. Abstract: In this study, predictions of the E-CHAIM ionospheric model are compared with measurements by the incoherent scatter radars RISR at Resolute Bay, Canada, in the northern polar cap. Reasonable coverage was available for all seasons except winter for which no conclusions were drawn. It is shown that ratios of the model-to measured electron densities are close to unity in the central part of the F layer, around its peak. This is particularly evident for summer daytime. Distributions of the ratios are wider for other seasons indicating larger number of cases when the model underestimates or overestimates. E-CHAIM underestimates the electron density at ionospheric topside and bottomside by ∼ 10–20 %. At the bottomside, the underestimations are strongest in summer and equinoctial nighttime. At the topside, the underestimations are strongest in autumn nighttime. Model overestimations are noticeable in the middle part of the F layer during dawn hours in autumn. Overall, the model tends to not predict highest-observed peak electron densities and the largest-observed heights of the peak.